Tinjauan Tingkat Kematangan Karir Mahasiswa (Studi pada Mahasiswa Program Studi BK Universitas PGRI Sumatera Barat) - Yasrial Chandra; Rahmawati Wae (Departement of Mathematics Education, 2023)
The problem in this research is motivated by the presence of PGRI University West Sumatra BK Study Program students who have not been able to make decisions or carry out activities that support career planning. This study aims to uncover and reveal and describe the level of student career maturity. This type of research is descriptive quantitative, with a sample of 67 students from batch 2019 at PGRI University, West Sumatra. Data was collected using a questionnaire and analyzed using the percentage technique of the average. The results of the study revealed that career maturity in college students is generally in a fairly high category with a percentage of 32.84%. For this reason, there is a need for special studies and attention related to efforts to achieve the level of student career maturity through various forms of career guidance services.